Development of Student Worksheets Based on Scientific Literacy in the Food Digestion System Subject of Class XI Science High School - Siti Hafsah Harahap; Wan Syafi’i; Sri Wulandari (Journal of Educational Sciences, 2020)
This study aims to develop student worksheets (LKPD) based on scientific literacy on the digestive system subject of class XI IPA high school. The small group test was conducted at SMAN 4 Dumai, because the LKPD used so far had not been based on scientific literacy so the scientific literacy ability of students was still low. This type of research was a research and development model of Borg and Gall. The validity instruments were the RPP, the LKPD, and the question validation sheets. The practicality instrument was a questionnaire of teacher and student responses. The validator consists of 2 lecturers (subject and education experts) and 2 teachers (practitioners). The data obtained is qualitative data converted to quantitative data. RPP validation results from 7 aspects of 3.8 (valid). LKPD validation of 3.77 (valid) includes content aspects of 3.92, linguistic 3.63, content 3.67, and characteristics of 3.85. LKPD is classified as practical after being tested on 15 class XII science students who have received food digestion subject before. The results of the response of students by 3.51 from 3 aspects, namely subject, language and presentation. The results of teacher responses amounted to 3.77. It can be concluded that the LKPD developed is feasible and practically used in the learning process.